Exporting and offshoring with monopsonistic competition - Hartmut Egger; Udo Kreickemeier; Christoph Moser; Jens Wrona (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
We develop a model of international trade with a monopsonistically competitive labour market in which firms employ skilled labour for headquarter tasks and unskilled workers to conduct a continuum of production tasks. Firms can enter foreign markets through exporting and through offshoring, and we show that due to monopsonistic competition our model makes sharply different predictions, both at the firm level and at the aggregate level, about the respective effects of the export of goods and the offshoring of tasks. At the firm-level, exporting leads to higher wages and employment, while offshoring of production tasks reduces the wages paid to unskilled workers as well as their domestic employment. At the aggregate level, trade in goods is unambiguously welfare increasing since domestic resources are reallocated to large firms with high productivity, and firms with low productivities exit the market. This reduces the monopsony distortion present in autarky, where firms restrict employment to keep wages low, resulting in too many firms that are on average too small. Offshoring on the other hand gives firms additional scope for exercising their monopsony power by reducing their domestic size, and as a consequence the resources spent on it can be wasteful from a social planner's point of view, leading to a welfare loss.
Keywords: F12; F16; F23; 330; Monopsonistic labour markets; Exporting; Two-way offshoring; Tasks; Heterogeneous firms; Wages; Employment